K.I. PANGALO'S SCIENTIFIC HERITAGE AND HIS ROLE IN THE DEVELOPMENT OF N.I. VAVILOV'S IDEAS IN STUDYING AND USING THE WORLD COLLECTION OF CUCURBITACEOUS CROPS IN BREEDING - G. A. Tekhanovich (Труды по прикладной ботанике, генетике и селекции)
Presented here is the information about the life and scientific activities of K.I. Pangalo, a scientist famous for his research on cucurbitaceous crops, a friend and companion of N.I. Vavilov.